2016
DOI: 10.4037/ajcc2016695
|View full text |Cite
|
Sign up to set email alerts
|

Communicating While Receiving Mechanical Ventilation: Texting With a Smartphone

Abstract: Two young adults with severe facial injuries were receiving care in the trauma/surgical intensive care unit at a tertiary care, level I trauma center in the southeastern United States. Both patients were able to communicate by texting on their cellphones to family members, friends, and caregivers in the intensive care unit. Patients who are awake and already have experience texting with a smartphone or other electronic handheld device may be able to communicate well while receiving mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In the CS, the identification of the need for communication training programmes for ICU staff, especially for communicating with non-verbal patients, is consistent with the findings of other studies (Magnus & Turkington, 2006;Shiber et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the CS, the identification of the need for communication training programmes for ICU staff, especially for communicating with non-verbal patients, is consistent with the findings of other studies (Magnus & Turkington, 2006;Shiber et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Also, partial or complete tube cuff deflation with digital occlusion, plugging or capping of the tube, a one-way speaking valve and tracheostomy button were used. In addition, other measures were found in other studies (Flinterud & Andershed, 2015;Morris et al, 2015;Pina et al, 2020;Shiber et al, 2016;Ull et al, 2020). The use of such devices, however, is predicated on the ability of the patient to be able to use them.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…One study was specific to mothers [ 40 ] and one study was specific to fathers [ 45 ]. Few studies reported additional perspectives from members of the clinical care team (e.g., nurses, primary care physicians) (n = 3, 10%) [ 29 , 34 , 50 ] or critical care patients (n = 3, 10%) [ 22 , 28 , 49 ]. More than half of the studies examined real-time communication platforms (e.g., FaceTime, Skype) (n = 17, 55%) [ 23 , 24 , 28 , 30 40 , 47 , 51 , 52 ], which accounted for many of the studies conducted with adult populations (3/7, 43%) and most of the studies conducted with neonatal or pediatric populations (14/22, 64%).…”
Section: Resultsmentioning
confidence: 99%
“…primary care physicians) (n = 3, 10%) [29,34,50] or critical care patients (n = 3, 10%) [22,28,49]. More than half of the studies examined real-time communication platforms (e.g., Face-Time, Skype) (n = 17, 55%) [23, 24, 28, 30-40, 47, 51, 52], which accounted for many of the studies conducted with adult populations (3/7, 43%) and most of the studies conducted with neonatal or pediatric populations (14/22, 64%).…”
Section: Plos Onementioning
confidence: 99%